EBV-RELATED LYMPHOPROLIFERATIVE DISEASES: A REVIEW IN LIGHT OF NEW CLASSIFICATIONS - Pietro Tralongo; Arianna Bakacs; Luigi Maria Larocca (Mediterranean Journal of Hematology and Infectious Diseases)
Epstein-Barr virus (EBV) is a prevalent virus that can be detected in the vast majority of the population. Most people are asymptomatic and remain chronically infected throughout their lifetimes. However, in some populations, EBV has been linked to a variety of B-cell lymphoproliferative disorders (LPDs), such as Burkitt lymphoma, classic Hodgkin lymphoma, and other LPDs. T-cell LPDs have been linked to EBV in part of peripheral T-cell lymphomas, angioimmunoblastic T-cell lymphomas, extranodal nasal natural killer/T-cell lymphomas, and other uncommon histotypes. This article summarizes the current evidence for EBV-associated LPDs in the light of the upcoming World Health Organization classification and the 2022 ICC classification.